2005
DOI: 10.1007/s00122-005-0008-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SCAR markers linked to Rca2 anthracnose resistance gene and their assessment in strawberry germplasm

Abstract: Bulked segregant analysis combined with AFLPs was used to identify molecular markers linked to the Rca 2 gene conferring resistance to Colletotrichum acutatum pathogenicity group 2 which causes anthracnose in the octoploid strawberry Fragaria x ananassa. DNA bulks originating from a cross between the resistant cultivar 'Capitola' and the susceptible cultivar 'Pajaro' were screened with 110 EcoRI/M se IAFLP combinations. Four AFLP markers were found linked in coupling phase to Rca 2 with recombination percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 26 publications
0
30
0
3
Order By: Relevance
“…The mapping studies performed in the cultivated strawberry have highlighted regions of extensive homozygosity in the genomes of modern F. ×ananassa cultivars attributed to repeated cycles of breeding and selection of specific loci, as well as rearrangements between the diploid and octoploid genomes [8,10]. Despite the molecular resources that have been developed for the cultivated strawberry, to date, only a few studies have reported the characterization of traits of economic importance [12][13][14][15][16], one of the main difficulties being finding sufficient numbers of markers to efficiently saturate QTL-containing regions of the genome.…”
Section: Introductionmentioning
confidence: 98%
“…The mapping studies performed in the cultivated strawberry have highlighted regions of extensive homozygosity in the genomes of modern F. ×ananassa cultivars attributed to repeated cycles of breeding and selection of specific loci, as well as rearrangements between the diploid and octoploid genomes [8,10]. Despite the molecular resources that have been developed for the cultivated strawberry, to date, only a few studies have reported the characterization of traits of economic importance [12][13][14][15][16], one of the main difficulties being finding sufficient numbers of markers to efficiently saturate QTL-containing regions of the genome.…”
Section: Introductionmentioning
confidence: 98%
“…Linkage mapping investigations in the cultivated strawberry have identified major genes and quantitative trait loci (QTL) for a number of agronomic traits, including disease resistance (Lerceteau-Kohler et al 2005), flowering habit (Sugimoto et al 2005;Weebadde et al 2008) and traits associated with fruit quality (Zorrilla-Fontanesi et al 2011a). However, these studies have often employed marker types that are not easily transferrable between mapping progenies, or traits have been identified in regions where no transferrable molecular marker loci have been located.…”
Section: Introductionmentioning
confidence: 99%
“…The first gains that will come from a sequenced genome will be from identification of molecular markers, easily traceable DNA patterns that associate with a trait of interest, complementing the current set available in strawberry (Whitaker, 2011). For example, it is possible to amplify a short piece of DNA in plants that tend to be resistant to anthracnose fruit rot, caused by Colletotrichum acutatum (Lerceteau-Kohler et al, 2005). Plants containing this fragment are resistant to the disease, whereas susceptible plants fail to permit amplification.…”
Section: How Will the Sequence Impact Consumers?mentioning
confidence: 99%